Therapeutic Angiogenesis - Higashi, Yukihito; Murohara, Toyoaki (Springer Singapore : Imprint: Springer, 2017)
The book discusses recent findings and current perspectives on therapeutic angiogenesis. Studies have shown that therapies such as cell implantation and transfer of gene encoding for angiogenic growth factors are effective in improving symptoms in patients with critical limb ischemia, who previously had no treatment option other than amputation. The book discusses these therapies and presents data collected in clinical studies over the past decade. Despite significant advances in therapeutic angiogenesis since the first clinical studies in the early 21st century, it has been largely ignored in the literature. This comprehensive book fills that gap, making it a valuable resource for both researchers and practitioners alike.